Longitudinally extensive transverse myelitis after Campylobacter jejuni enteritis. Issue 2 (22nd December 2017) - Llamas, Yudy; Hazel, Karl; Nicholson, Patrick; Costelloe, Lisa
Abstract : Campylobacter jejuni infection is well-known to precipitate Guillain-Barré syndrome through an immune-mediated attack on the peripheral nervous system. Molecular mimicry between C. jejuni lipo-oligosaccharides on the surface of infectious agents and human gangliosides in the peripheral nerves induces cross-reactive immune responses. Although gangliosides also occur in the central nervous system (CNS), autoimmune CNS disorders rarely follow C . jejuni infections. However, longitudinally extensive transverse myelitis commonly has a parainfectious cause, triggered by a wide range of micro-organisms including viruses and bacteria. We report a patient who developed longitudinally extensive transverse myelitis after C . jejuni enteritis associated with antiganglioside antibodies.